The Bergen 4-Day Treatment for Panic Disorder: A Pilot Study - Hansen, Bjarne; Kvale, Gerd; Hagen, Kristen; Hjelle, Kay M.; Solem, Stian; Bø, Beate; Öst, Lars-Göran (Frontiers in Psychology, 2018)
The current article reports on the findings from a pilot treatment study on panic disorder (PD) with or without agoraphobia. Consecutively referred patients were included and treated with the Bergen 4-day treatment format. Twenty-nine patients were included, primarily from unsuccessful treatment courses in the Norwegian specialist mental health care system, either ongoing or previously. Prior to treatment, only 34% were able to work but at 3-month follow-up 93% were able to do so. The proportion achieving reliable change on the panic severity measure was 76% post-treatment and 90% at follow-up. The remission rate was 72% at both assessments. These effects are significantly higher than those reported for six standard CBT studies in the literature using the same primary outcome measure (Panic Disorder Severity Scale). It is concluded that the Bergen 4-day treatment is a promising treatment approach for PD, and a randomized controlled trial is warranted.